Degradation of Imidacloprid by Bacteria Isolated from Contaminated Sites - Arora, Rabia (My University, 2012)
The rapidly growing industrialization along with an increasing population has resulted in the accumulation of a wide variety of chemicals. Pesticides are used in sizeable areas and applied to soil surfaces and accumulate beneath the ground surface, reaching rivers and seas thus contaminating ground water which is harmful for the entire ecosystem. The effect of concentration of imidacloprid on the degradation kinetics was studied by inoculating the two bacterial strains C-5 and C-9 in minimal media with imidacloprid concentration of 50,100, and 150 mg/l. the effect of ph on imidacloprid degradation was observed. More the drop in pH, more was the microbial activity of isolated bacterial strains C-5 and C-9 which results in more imidacloprid degradation. Degradation of imidacloprid was reported more in lower concentration of 50 mg/l as the higher concentration of imidacloprid was reported to be toxic for some microorganisms. Thus the inability of the microorganisms to use imidacloprid as a sole carbon source was effected due to change in the metabolism of microbes. C-9 was found out to be more efficient in degrading imidacloprid. Similarly the degradation of imidacloprid was also observed in soil microcosm experiment.
Keywords: Imidaclorpid; Degradation; Bacteria